IMPLEMENTASI PENGUATAN PENDIDIKAN BERBASIS KARAKTER DI SEKOLAH DASAR - Agus Wijayanto; Daryono; Mochamad Bayu Firmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to describe the implementation of character education in the formation of students' holistic personality. The research was a qualitative study conducted at SDN Pasrepan III Kecamatan Pasrepan Kabupaten Pasuruan. Data were obtained from in-depth interviews with key informants : principals, teachers, and students parents. Data were analyzed by using the steps of data reduction, data display, and conclusion/verification. Based on the results of the data analysis, the research showed that: (1) the management of character education could be divided into two strategies, namely internal and external; (2) the internal strategy of the school could be accomplished through the four pillars, namely teaching and learning activities in the classroom, daily activities in the form of school culture, habit formation activities, curricular and extra-curricular activities; and (3) external strategy could be done by cooperating with parents and the community.